The effect of Saccharomyces cerevisiae on the serum creatinine levels of chronic kidney disease mice model - besut daryanto (Journal of Global Pharma Technology, 2019)
Title: The Effect of Saccharomyces Cerevisiae On The Serum Creatinine Levels of Chronic Kidney Disease Mice Model Besut Daryanto, M.D, Ph.D *, Givary Dymar Lazuardi, Dewi Mustika, M.DDepartment of Urology, Faculty of Medicine, Universitas Brawijaya, Indonesia*Author: Email: besut.daryanto@yahoo.co.idTel.: +628123104879; Fax: +62341333030 AbstractIntroductionChronic kidney disease is pathological condition with various causes, resulting in a progressive loss in kidney function and then ended in end-stage kidney disease. Chronic Kidney Disease become a health problem in the world with increasing number of patients, high progressivity, and bad prognosis. Saccharomyces cerevisiae which has high beta glucan content can increase the level of granulocyte-colony stimulating factor (G-CSF) in the body. The increase of G-CSF level will elevate the excess of hematopoietic stem cell (HSC) in the circulation. The excess HSC can regenerate damaged tubular cells. The study used serum creatinine levels as a marker of improved kidney function. The objective of this research is to determine the effect of S. cerevisae to the serum creatinine levels of mice model with chronic kidney disease and to determine the correlation between dose of S. cerevisae extract and serum creatinin levels of chronic kidney disease mice model.Materials & MethodsThis in vivo experimental study used a randomized post test only controlled group design. The samples were divided into five groups, each group consists of 5 mice, that were negative control group, positive control group, Treatment Group 1 (Aristolochic Acid + S. cerevisae extract 50 mg/kg), Treatment Group 2 (Aristolochic Acid + S. cerevisae extract 100 mg/kg), Treatment Group 3 (Aristolochic Acid + S. cerevisae extract 200 mg/kg). The induction of chronic kidney disease were using aristolochic acid 2,5 mg/KgBW 5 times a week for 2 weeks. The variables measured in this research is the serum creatinine levels.ResultsStatistical data obtained shows that the average number of serum creatinine levels at negative control group was 0,3788 mg/dl in the positive control was 0,6425 mg/dl; in the treatment 1 was 0,4575 mg/dl; in the treatment 2 was 0,3850 mg/dl; in the treatment 3 was 0,3263 mg/dl. ANOVA test results showed significant difference between groups (p < 0.05)Conclusions S. cerevisae was able to decrease the serum creatinine levels of chronic kidney disease mice model and there were correlation between increased dose of S. cerevisae and decreased in serum creatinine levels. Keywords Beta Glucan, Saccharomyces cerevisae, serum creatinine levels, Chronic Kidney Disease